IMPORT SUBSTITUTION AS A FORM OF EFFECTIVE ECONOMIC POLICY OF THE RUSSIAN GOVERNMENT - E. A. Yakovleva; E. A. Kozlovskaya (Финансы: теория и практика)
Today, like never before, the need for import substitution in the Russian industry to ensure the preservation and growth of the country’s economic potential as well as the promotion of Russian products on the international market is in the limelight. It is noted that the integration processes should be enhanced through development of the technological audit which can provide customers with new relevant R&D information, analyze it, choose the most promising designs, and promote the commercialization of innovations along with reducing risks associated with the selection of innovative projects. The role of the state in the import substitution process is demonstrated; the foreign experience of solving organizational problems in the process of the innovation development is described. It is concluded that the import substitution should be aimed at the creation of a competitive environment in the country to be able to compete with foreign counterparts.